Analisis Sentimen Keluhan Pengguna pada Game Mobile Legends Menggunakan Metode K-Means Clustering - Orlando, Nikolas; Prasetya, Benedikto Nugroho; Hermawan, Latius (MDP Student Conference, 2025)
Mobile Legends is a popular mobile game, but many users express complaints about their gaming experience. This study aims to analyze user complaints’ sentiment using the K-Means Clustering method to group data based on similar complaint patterns. The data was collected from user reviews on the Google Play Store. The results indicate that the K-Means method effectively categorizes complaints into major issues such as connection problems, in-game bugs, and character imbalance. This analysis helps developers identify key user concerns and improve the gaming experience.